Penyuluhan Uji Kualitas Air Sumur Menggunakan Parameter Fisika di Desa Kertosari - udrika lailatul qodri (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Clean water used as a source of drinking water must meet eligibility criteria based on chemical, physical and biological parameters. Physical parameters such as pH, temperature, TDS, and EC are very easy to apply directly in the analysis of well water quality in community outreach activities in the village of Kertosari. This activity is important because water wells are found in almost every villager's house and are used as drinking water and for cooking. well water in Kertosari village has never been tested for water quality as good water for consumption. Counseling on testing the quality of residents' well water will provide information on the feasibility level as drinking water based on physical test parameters. Drinking water quality tests were carried out in 31 areas in Kertosari which were carried out by well owners. 5 of them have good drinking water quality standards based on physical parameters. This activity is very useful and becomes important information for residents with the percentage value of the results of filling out the questionnaire on the respondent's satisfaction variable is 96% and the speaker's ability to provide information is 93%. so this activity goes well.